Determinación de la cantidad de combustibles forestales presentes en el bosque nativo del Parque Universitario Francisco Vivar Castro, Loja, Ecuador - Oña Gualotuña, Evelyn Fabiola (2021)
The diversity of ecosystems in the tropics is exuberant and Ecuador, due to its territorial location, is considered one of the megadiverse countries in the world, its environmental and geographical conditions produce different quantities and qualities of fuels, which is one of the elements for the existence on fire. This research was conducted in the university park "Francisco Vivar Castro", belonging to the National University of Loja, located in the canton and city of Loja, with an approximate area of 99 ha. The general objective was to contribute to the knowledge of fire behavior by determining the amount of forest fuels in the andean forests that can be used as an input for integrated fire management. Twenty-four temporary plots of 20 m x 20 m, divided into two sections of 10 m x 20 m, we recorded information, such as light, small light, medium, and heavy (firm and rotten) dead forest fuels, using the method of intersecting lines. To determine the number of dead fuels, formulas were used that required variables such as specific weights of each type of fuel, slope correction factor, the sum of squared diameters of branches or logs, and the sum of lengths of the intersecting lines. To estimate the number of live forest fuels information was collected on the diameters of each individual with DBH ≥ 5 cm, and subsequently, the aerial and root biomass was calculating using allometric equations. The total quantity of dead fuels was 32,53 Mg ha-1, the medium fuels had the highest load with a total of 7,60 Mg ha-1, and the litter had the lowest load of 3,55 Mg ha-1. We recorded 900 individuals, 46 species, 36 genera, and 27 families, and the total amount of live forest fuel was 116,52 Mg ha-1, the aerial biomass has a total of 89,63 Mg ha-1, and the root biomass a total of 26,89 Mg ha-1. The species with the highest fuel content were Alnus acuminata Kunth with 67,50 Mg ha-1 and Oreopanax rosei Harms with 10,52 Mg ha-1, both represented 67 % of the total live fuel biomass, while Acalypha diversifolia Jacq., Mauria heterophylla Kunth, Miconia sp., Baccharis latifolia (Ruiz & Pav.) Pers, and Oreopanax andreanus Marchal are the ones that registered amounts lower than 0,02 Mg ha-1. The highest quantities of live and dead forest fuels were concentrated in the middle parts of the native forest, where it is in a better state of conservation. Pearson's correlation coefficient (r = 0,57 and a significant p value of 0,0039) identified a moderate positive association between live and dead fuels. The total quantities of live and dead forest fuels recorded for the native forest of the university park constitute the basis for the initiation of research related to integrated fire management since the presence of these fuels in different amounts and proportions make the forest a potential scenario for a forest fire. Key words: forest, fuel, litter, biomass, fire.